Religious (de)politicisation in Uganda's 2016 elections. Issue 4 (1st October 2016) - Alava, Henni; Ssentongo, Jimmy Spire
ABSTRACT: Religion has influenced Ugandan politics ever since colonial times. While the interrelations of religion and politics have altered since the coming to power of president Museveni's National Resistance Movement (NRM), religion continues to influence Ugandan public culture and formal politics in important ways. Building on ethnographic fieldwork in Kampala and Acholi, as well as analysis of media reporting and discussions in social media, this article focuses on the role of religious leaders during Uganda's 2016 parliamentary and presidential elections. We argue that the striking differences between Ugandan clerics' teaching on politics relate in part to genuine differences in religious beliefs, but also to patronage, intimidation, and ethnicity, and to the strategic calculations religious leaders make about how best to affect change in a constricted political environment. In discussion with previous research on religion and politics in Africa, and utilising analytical concepts from the study of publics, the article proposes a model of religious (de)politicisation, whereby both the politicising and depoliticising effects of religion are acknowledged. To do so, the analysis distinguishes between NGO-ised and enchanted planes of religion, and shows that on both planes, religion contributed simultaneously to enhancing and diminishing the space for public debate in election-time Uganda. While many religious leaders actively or silently supported the incumbent regime, religious leaders also took vocal public stands, fostered political action, and catered for vernacular imaginaries of political critique, by so doing expanding the space of public debate. However, by performing public debate that remained vague on crucial issues, and by promoting a religious narrative of peace, religious leaders participated in the enactment of a façade of political debate, in so doing legitimising the autocratic facets of Museveni's hybrid regime. Acknowledging religion as an important constituent of public culture contributes to more nuanced understandings of election dynamics in Eastern Africa.